PENERAPAN SENSOR FLOAT MAGNETIC LEVEL GAUGE PADA SISTEM MONITORING LEVEL CAIRAN LIMBAH - Miranty, Miranty; Syam, F S; Opu, A.S (Foristek, 2024)
In the industrial world, especially in the metal processing sector, in this case in the steel roll production process, the problem faced is that controlling the pump motor in the hydraulic room is still done manually so that the waste water reservoir in the hydraulic room overflows which causes the floor to be slippery and dangerous. . By using the float magnetic level gauge method which consists of a reed switch as the main component to take height level readings. The neodymium magnet used in the buoy functions as a trigger to activate the reed switch when the buoy height reaches a certain level. The use of the voltage divider principle is to obtain variations in the sensor output voltage which is then converted into water level readings. The process of monitoring waste liquid levels uses LabVIEW software. Research has been tested in one of the departments in the metal processing industrial area which obtained the results that the sensor readings correctly provide an output signal to the microcontroller which functions as a relay controller which activates the drain pump motor when it reaches full level. With a monitoring system, users can control the system via computer without having to go directly to the field to activate the pump motor manually